Transcriptome Analysis of Juvenile Tilapia (Oreochromis niloticus) Blood, Fed With Different Concentrations of Resveratrol - Zheng, Yao; Wu, Wei; Hu, Gengdong; Qiu, Liping; Chen, Jiazhang (Frontiers in Physiology, 2020)
Oreochromis niloticus (genetically improved farmed tilapia, GIFT) often bites the root of Polygonum cuspidatum when it is used as a floating bed, and resveratrol (RES) is mainly accumulated in the root of P. cuspidatum. Blood acts as a pipeline for the fish immune system. Generating blood transcriptomic resources is crucial for understanding molecular mechanisms underlying blood immune responses. In this study, we determined the effects of RES administration on blood transcriptomic response in GIFT. With increasing RES concentration, 133 (0.025 vs 0.05 g/kg RES), 155 (0.025 vs 0.1 g/kg RES), and 123 (0.05 vs 0.1 g/kg RES) genes were detected as significant differentially expressed genes (DEGs). Three and 95 shared significant DEGs were found to be enriched among the three (except 0.1 g/kg RES) and four groups (0, 0.025, 0.05 and 0.1 g/kg RES) respectively. To determine the relationship between mitochondrial regulation and RES supplementation, the results of RNA-Seq were analyzed and nine mitochondria-related genes (ATP synthase or mitochondrial-function-related genes) were verified. The results revealed the same expression pattern: cox2, katna1, atp2b1 and gtpbpal showed the highest expression in the 0.1 g/kg RES group, while nad7, atpb, atpal, atpa and clpp revealed a dose-dependent expression following RES supplementation. Blood Ca2+-ATPase activity, and malondialdehyde, glutathione, and ATP content were significantly increased in the 0.1 g/kg RES group when compared with the controls. Eighty-nine shared DGEs were mainly enriched in antigen processing and presentation, cell adhesion molecules and phagosome pathways, based on the comparison between previous reported hepatic and the present blood transcriptome. Our study demonstrated that RES supplementation might improve the resistance to metabolism dysfunction via mitochondrial energy synthesis and/or the respiratory chain (e.g. ATPase).